The influence of eggshell as coarse aggregate replacement in hot mix asphalt - Ng, Cui Ming; Putra Jaya, Ramadhansyah; Haryati, Awang (Penerbit UMP, 2021)
Hot Mix Asphalt (HMA) is the most commonly used in Malaysia for highways, interstates and roads due to its flexibility, economical, strong and provide safe riding quality for road users. Over the years, the increase of damage on pavement roads in Malaysia has become a severe issue although the road did not achieve its design life. Hence, to reduce damage and defect, an improvised road pavement structures is needed. Various studies have been conducted to identify the new materials that can be used as a replacement in hot mix asphalt. In this research, the purpose is to evaluate the performance of eggshell as coarse aggregate replacement in hot mix asphalt. The gradation for aggregate used in this mixture is AC14. The weight for total mixing of the aggregates used is 1200g while the grade for bitumen is 60/70. The samples were mixed with eggshell in the various percentages of 0%, 5%, 10%, 15% and 20% by total weight of aggregate size 5mm. The laboratory tests carried out to determine the properties of aggregates included, aggregate impact value and aggregate crushing value. Besides, penetration and softening point were also performed to determine the properties of bitumen. Several types of test were conducted towards the samples, which are Marshall Test, Indirect Tensile Strength and Cantabro Test. The results exhibit that the conventional asphalt mixture is more effective than modified asphalt mixture. The replacement of eggshell as coarse aggregate was not enough improvement to the performance of asphalt pavement as the performance of conventional mixture is more stable than modified mixture.